The Natural History of a Branch Duct Intraductal Papillary Mucinous Neoplasm in a Patient with Lady Windermere Syndrome: A CASE REPORTS - Nguyen, Vien X; Decker, G Anton; Das, Ananya; Harrison, M Edwyn; Silva, Alvin C; Ocal, Idris T; Collins, Joseph M; Nguyen, Cuong C (JOP. Journal of the Pancreas, 2010)
Context "Low-risk" branch duct intraductal papillary mucinous neoplasm (IPMN) is defined as pancreatic epithelial cellular proliferation of small branch ducts that lack malignant characteristics. At present, our understanding of the natural history of "low-risk" branch duct IPMN is still evolving. Lady Windermere syndrome is a disorder seen in non-smoking women with no pre-existing pulmonary disease affecting the lingula and/or right middle lobe with Mycobacterium avium-intracellulare complex. We present a case with pancreatic adenocarcinoma after a six-year surveillance of "low-risk" branch duct IPMN in an asymptomatic elderly white woman with Lady Windermere syndrome. Case report A 79-year-old woman was referred to our institution because of pancreatic cystic abnormalities and elevated carbohydrate antigen 19-9 (CA 19-9). While at our institution, she was also diagnosed with Lady Windermere syndrome. Multiple abdominal imaging studies, endoscopic retrograde cholangiopancreatography, computer tomography, and magnetic resonance cholangiopancreatography (MRCP) were performed in the ensuing 6 years, all consistent with "low-risk" branch duct IPMN. No progression was seen until year 6 when MRCP showed a 2 cm pancreatic cancer. Because of multiple comorbidities, the patient chose chemotherapy over a pancreaticoduodenectomy. She developed respiratory failure and died after one cycle of gemcitabine. Conclusions "Low-risk" branch duct IPMN may be a heterogeneous disease in which some cases can transform into malignant pancreatic neoplasms despite the absence of the so-called "high risk" features on imaging studies. Clinical management, therefore, requires individualized flexibility. In addition, when there is coexistence of Lady Windermere syndrome and pancreatic cancer, prompt diagnosis and treatment of Lady Windermere syndrome should be considered prior to chemoradiotherapy or surgery. Image: CA 19-9 level during follow-up of "low-risk" branch-duct IPMN.